THE CLINICAL PICTURE AND LABORATORY WORK-UP OF GLANZMANN THROMBASTHENIA - Joanna Zdziarska; Teresa Iwaniec; Tomasz Sacha; Ewa Wypasek (Hematology, Transfusion and Cell Therapy, 2021)
Case report: We present the clinical picture and laboratory work-up of Glanzmann thrombasthenia, based on a group of 7 patients. Bleeding history was significant in all patients and included both mucosal and postsurgery bleeds. Laboratory analysis revealed decreased or absent platelet aggregation (< 10%) with all physiologic agonists (ADP, collagen, epinephrin, arachidonic acid) together with normal agglutination response to ristocetin. In three patients diagnosis was confirmed by flow cytometry.